Segmented relations between online reading behaviors, text properties, and reader–text interactions: An eye-movement experiment - Gong, Tao; Shuai, Lan (Frontiers in Psychology, 2023)
Purpose: To investigate relations between abilities of readers and properties of words during online sentence reading, we conducted a sentence reading eye-movements study on young adults of English monolinguals from the U.S., who exhibited a wide scope of individual differences in standard measures of language and literacy skills. Method: We adopted mixed-effects regression models of gaze measures of early and late print processing stages from sentence onset to investigate possible associations between gaze measures, text properties, and skill measures. We also applied segmented linear regressions to detect the dynamics of identified associations. Results: Our study reported significant associations between (a) gaze measures (first-pass reading time, total reading times, and first-pass regression probability) and (b) interactions of lexical properties (word length or position) and skill measures (vocabulary, oral reading fluency, decoding, and verbal working memory), and confirmed a segmented linear dynamics between gaze measures and lexical properties, which was influenced by skill measures. Conclusion: This study extends the previous work on predictive effects of individual language and literacy skills on online reading behavior, enriches the existing methodology exploring the dynamics of associations between lexical properties and eye-movement measures, and stimulates future work investigating factors that shape such dynamics.